MUHAMMADIYAH SCHOOL MANAGEMENT STRATEGY IN BANGKA BELITUNG - Sri Sugiyarti; Muhammad Iqbal Arrosyad (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
The charitable endeavors of Muhammadiyah in the Bangka Belitung Region in the field of education from the levels of Elementary Schools, Junior High Schools, and High Schools and Vocational High Schools are spread to all districts/cities. However, the discussion about Muhammadiyah education in Bangka Belitung is very minimal. This research is a descriptive study with a qualitative approach. This study took the sample of the oldest and best senior high school as an illustration of Muhammadiyah education management in Bangka Belitung. The results showed that Muhammadiyah Education experienced various obstacles to the threat of closure, however, they were able to rise from adversity. Muhammadiyah Pangkalpinang High School as the oldest school departed from a school that boarded at Muhammadiyah Middle School and later became one of the most popular schools in the era of the 1990s to accommodate students up to 18 classes, but later it fell free and was almost closed due to the lack of students. Several times the change of school principals has not improved, a new hope is obtained when the management of this school is submitted to the STKIP Muhammadiyah Bangka Belitung to become its lab school. Now with new facilities and management, the number of students is increasing, slowly but surely this school is starting to improve itself. Meanwhile, Muhammadiyah Toboali High School, South Bangka Regency, which was established in 1994, almost lost public confidence, due to a large number of students who failed the National Examination for the 2006/2007 school year. The situation changed along with Supiandi's leadership, his persistence in managing the school, and finally, the trust in the community returned. Now the number of students has reached nearly 500 students